New strategies in angioprotective therapy for patients with Type 2 diabetes mellitus and arterial hypertension - A. S. Ametov; T. Yu. Demidova; S. A. Kosykh (Российский кардиологический журнал)
In 30 patients with Type 2 diabetes mellitus (DM) and mild to moderate arterial hypertension (AH), hypotensive, antiischemic efficacy, and influence on endogenous protective systems (NO, heat shock proteins HSP 70) of a new, third-generation, cardio-selective NO-modulating beta-blocker nebivolol (nebilet) were studied. For 16 weeks, participants received nebivolol as monotherapy (2. 5-5-10 mg/d). Significant hypotensive, anti-ischemic effects of nebivolol, as well as increased endothelial NO secretion and HSP 70 synthesis, were demonstrated.